2020
DOI: 10.1038/s41598-020-64159-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and ecology of coronaviruses hosted by cave-dwelling bats in Gabon

Abstract: Little research on coronaviruses has been conducted on wild animals inAfrica. Here, we screened a wide range of wild animals collected in six provinces and five caves of Gabon between 2009 and 2015. We collected a total of 1867 animal samples (cave-dwelling bats, rodents, non-human primates and other wild animals). We explored the diversity of CoVs and determined the factors driving the infection of CoVs in wild animals. Based on a nested reverse transcription-polymerase chain reaction, only bats, belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 58 publications
5
36
1
Order By: Relevance
“…It also confirms the observations from the large study on CoVs in more than 12,000 bats across Africa and Asia from Anthony et al (2017) who demonstrated that increasing sampling efforts leads to increased identification of new lineages. Although we studied only very few samples from Hipposideros bats, we did not only find a high infection rate (7/21, 33%), but observed also a high genetic diversity among their CoVs in accordance with most previous studies on Hipposideros species in Africa [ 15 , 34 , 35 , 39 , 40 , 41 , 42 ]. The human 229E α-CoV falls in a clade of bat CoVs that is widely present in Hipposideros bats from Kenya, Zimbabwe, Mozambique, Gabon, Ghana and also in our study in Guinea.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It also confirms the observations from the large study on CoVs in more than 12,000 bats across Africa and Asia from Anthony et al (2017) who demonstrated that increasing sampling efforts leads to increased identification of new lineages. Although we studied only very few samples from Hipposideros bats, we did not only find a high infection rate (7/21, 33%), but observed also a high genetic diversity among their CoVs in accordance with most previous studies on Hipposideros species in Africa [ 15 , 34 , 35 , 39 , 40 , 41 , 42 ]. The human 229E α-CoV falls in a clade of bat CoVs that is widely present in Hipposideros bats from Kenya, Zimbabwe, Mozambique, Gabon, Ghana and also in our study in Guinea.…”
Section: Discussionsupporting
confidence: 90%
“…and two frugivorous species (4/9 Eidolon helvum and 1/1 Nanonycteris sp.). However, it cannot be excluded that this could be related to the season when samples were collected, for example several studies have shown temporal variations of CoV infections associated with parturition [ 37 , 41 , 53 , 54 , 55 ]. Longer follow-up should be done on these bat species in Guinea to assess temporal dynamics of CoV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They may cause wider diseases with different levels of severity in a variety of hosts. It is essential to investigate proximal origin [1], probable intermediate hosts [2], evolutionary conservation [3,4], genetic diversity of Bat [5][6][7], genome-based classification/phylogenies [8,9], genetic evolution analysis [10] and coronavirus mutations affecting deadliness of strains [11] for medical treatments of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%